Perjanjian Indonesia-Malaysia Terhadap Tki (Tenaga Kerja Indonesia) Yang Ditinjau Dari Segi Hukum Dan Ekonomi - Claudya Florenza Br Rajagukguk; Annisa Ayu Syahrani; Tamaulina Br Sembiring (Jurnal Multidisiplin Indonesia, 2024)
In social life, humans are called social creatures, which means that humans cannot live alone. Humans need help or assistance from other humans in order to survive. Just like humans, countries cannot stand alone without help from other countries. The independence of a country requires recognition from other countries so that the country can be said to be legally an independent country. In fact, not only in terms of independence, the country needs the role of other countries to be able to grow and strengthen the country. Due to the awareness that a country cannot stand alone, an agreement is made between one country and another country. This agreement is called an "International Agreement". An international agreement is an important agreement for one country with another country, because with the existence of an international agreement the possibility of cooperation with other countries opens up which ultimately creates peace between the countries involved in the agreement. Not only does it create peace, international agreements can also cover a country's shortcomings and open the way for cooperation with other countries. There are two characteristics of international agreements, namely bilateral and multilateral. Currently, Indonesia has established many cooperative relationships with other countries, one of which is with neighboring countries, namely Malaysia in the field of Indonesian Workers (TKI). To see how the cooperation between Indonesia and Malaysia has been agreed, the author has summarized it in the discussion of this article.